THE EFFECT of PROMOTION on IMPULSIVE BUYING with LIFESTYLE as a MODERATION VARIABLE on FASHION PRODUCTS in ONLINE SHOP SHOPEE - Untari, Dhian Tyas; Widyastuty, Iin (Journal of Economic Development, Environment and People, 2021)
The purpose of this study was to explain the effect of promotion on impulsive buyers and to explain that people with high lifestyles often make impulse purchases. Sampling using incidental sampling technique, the number of respondents as many as 100 respondents. The data collection method used is the observation method and the questionnaire method. Analysis of the data used is multiple linear regression analysis with moderating variables using the SPSS program. The results of the study prove that promotion has a direct effect on impulse buying and it is not proven that people with a high life style are more likely to make impulsive purchases.